(untitled) (Ustozlar uchun, 2024)
Abstract. This study investigates the impact of gender differences in decision-making on various outcomes. It analyzes how societal norms, cultural expectations, and psychological factors shape risk-taking, confidence, and decision preferences in personal and professional settings. Men often exhibit greater risk and confidence, benefiting leadership roles, whereas women's risk aversion and emotional considerations lead to cautious, thoughtful decisions. The findings highlight the importance of recognizing these differences to optimize outcomes in leadership, policymaking, and team performance.